Influence of Cashless Society Socialization toward Trust Transaction Culture in Jakarta, Indonesia - Hastomo, Arnoldus Dillon; Aras, Muhammad (Humaniora, 2018)
The research methods were using a quantitative approach with survey methods based on communication theories that made this an objective and in-depth study of the fact-data found in the field. Data analysis with the statistics program then entered into an interpretation of the meaning that connected between indicators in variable X namely Cashless Society Socialization and variable Y namely Trust Transaction Culture. The research results show that the socialization through repressive ways that have been considered not popular in the community turns out to have a strong effect on the culture of trust non-cash transactions. Withoutruling out other indicators, this research reveals that the people of Jakarta are ready to accept their belief culture changes in society transacting in the modernization era.